Prevalence of diabetes mellitus among adults treated in Imo State University teaching hospital Orlu local government area, Imo State, Owerri, Nigeria - C., Ezeama Martina; E., Enwereji Ezinna (International Journal of Advances in Medicine, 2019)
Background: Type 2 diabetes is the result of complex interplay between genetic and environmental factors. Diabetes epidemic is largely due to unhealthy diet and lifestyles. Dietary composition affects both its development and complications because fatty acids influence glucose metabolism by altering cell membrane function, enzyme activity, insulin signalling, and gene expression. Therefore, replacing saturated fats and trans-fatty acids with unsaturated fats has beneficial effects on insulin sensitivity and in reducing the risks of type 2 diabetes. Research has shown that if people with diabetes, together with the health care workers manage diabetes well, that the risk of complications will be greatly reduced or prevented or delayed. This study focused on assessing the prevalence and causes of type 2 diabetes, types of complications patients presented, and the likely preventive interventions given to them in University Teaching Hospital Orlu. Methods: A retrospective study that carried out extensive review of hospital records of adults admitted and treated for type 2 diabetes mellitus from 2015 to 2017 in University Teaching Hospital was done. The review of the adult patients’ records lasted for three working weeks. In the review, summaries of causes of diabetes, types of complications and preventive measures health workers provided to the patients were documented. Results: Finding showed that 79 adults made up of 43(54.4%) males and 36(45.6%) female between 41-77 years were admitted and treated for various causes of type 2 diabetes between 2015 and 2017. Most of the patients treated were civil and public servants. The main cause of diabetes mellitus 51(65%) among the patients studied was physical inactivity due to sedentary work. The common complications presented were hypertension, diabetic ulcer, depression and obesity. Health talks and group counselling were the interventions provided. These interventions concentrated on types of healthy dietary intakes and lifestyles the patients should adopt. Conclusions: Regular and sustained health care services that would emphasize healthy diet and lifestyle modifications to reduce the risk factors of type 2 diabetes mellitus should be provided to all patients treated in this hospital. Therefore, obese diabetic patients should be encouraged to engage in physical exercises so as to maintain healthy body weight which is a cornerstone for prevention of type 2 diabetes mellitus.